Strategi Komunikasi Pemasaran Vivo Smartphone Dalam Membentuk Brand Awareness Di Kalangan Remaja Kelurahan Sei Putih Barat Kecamatan Medan Petisah - Fhadly Hermawan; Dedi Sahputra; Taufik Wal Hidayat (Universitas Medan Area, 2022)
The rapid development of technology creates an effective and efficient communication medium, namely smartphones. The increasing level of interest and smartphone users, a company from China issued a smartphone called Vivo. The rise of the Vivo brand started with Screen Touch Id technology (Fingerprint On the Screen) coupled with Agnes Monica's participation in promotional advertisements. Vivo has entered into the top three well-known brands around the world including Indonesia, especially the city of Medan. In increasing its popularity in Medan City, Vivo has developed an effective and efficient marketing communication strategy to build brand awareness of Vivo products among teenagers. This research is descriptive in nature, to find out the response of teenagers to Vivo related to its products and marketing communication strategies. Based on the results of the study, it can be concluded that Vivo uses product innovations that are different from other brands. Not only that, Vivo uses the marketing mix and promotion mix as a strategy and promotion to provide information and build brand awareness and provide an attractive effect on Vivo products.